Molecular markers and cytogenetics of Eleven O’Clock Portulaca umbraticola: a non-conventional edible ornamental crop - Souza, J. S. [UNESP]; Nunes, C. C.C.G.; Rêgo, M. M.; Santos, A. M.S.; Rodrigues, C. A.P.S.; Unêda-Trevisoli, S. H. [UNESP]; Rêgo, E. R. (FapUNIFESP (SciELO), 2024)
Portulaca umbraticola, commonly known as “Eleven o’clock”, is a popular ornamental plant in Brazil, but its potential as a non-conventional food source remains underexplored. Assessing its genetic and cytogenetic diversity is crucial for breeding and selecting optimal accessions. In this study, we analyzed the genetic diversity of P. umbraticola using RAPD markers and chromosomal traits in 20 accessions. We also compared them with P. oleracea to identify potential interspecific hybrids. Accessions were collected from Brazil and cultivated in 3L pots with commercial substrate. Controlled crosses and self-fertilizations were conducted in a greenhouse, followed by cytogenetic analyses. All amplified bands showed polymorphism among 18 accessions, indicating 100% polymorphism. The species displayed considerable dissimilarity, with all 20 accessions showing 2n = 18 chromosomes, while P. oleracea had 2n = 52 chromosomes. P. umbraticola exhibited allogamous reproduction tendencies and self-incompatibility, precluding self-fertilization. Analysis suggests that crosses between accessions 12 and 16 are recommended due to their substantial genetic distance. In conclusion, P. umbraticola and P. oleracea differ in chromosome numbers, and P. umbraticola shows allogamous reproduction with self-incompatibility.
Marcadores moleculares e citogenética de Eleven O’Clock Portulaca umbraticola: uma cultura ornamental comestível não convencional
Keywords: cytogenetic analysis; genetic diversity; Portulaca umbraticola; RAPD markers